The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/00219983211058796
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of impact-damaged carbon fiber–reinforced composites using induction heating

Abstract: Carbon fiber–reinforced composites (CFRCs) have been used extensively in structural applications within the aerospace and automotive manufacturing industries. However, several other applications have been recognized. These take advantage of the additional properties of CFRCs, which lead to providing better performance for structures. However, in their service environment, these CFRCs are inevitably susceptible to impact damage from multiple sources, and they must be able to recover from impacts to meet structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Rodgers and Mallon [18] CF/PEEK Induction heating to assess damage area Markus [21] CF/PEEK Induction heating to see if consolidation is possible Nijhuis [22] CF/PEEK Heat blanket with pressure and vacuum to see if viable Miyake and Takenaka [19] CF/PEEK Induction heating to assess the stiffness Toyoda et al [20] CF/PEEK Ultrasonic welding to assess bending stiffness Zorer et al [23] GF/PP Hot-press to evaluate impact response Bayazeid et al [24] CF/PEEK Induction heating to evaluate damage area and tensile strength…”
Section: Author Materials Repair Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Rodgers and Mallon [18] CF/PEEK Induction heating to assess damage area Markus [21] CF/PEEK Induction heating to see if consolidation is possible Nijhuis [22] CF/PEEK Heat blanket with pressure and vacuum to see if viable Miyake and Takenaka [19] CF/PEEK Induction heating to assess the stiffness Toyoda et al [20] CF/PEEK Ultrasonic welding to assess bending stiffness Zorer et al [23] GF/PP Hot-press to evaluate impact response Bayazeid et al [24] CF/PEEK Induction heating to evaluate damage area and tensile strength…”
Section: Author Materials Repair Techniquementioning
confidence: 99%
“…The study reported a better impact response with lower energy absorbed for the patched laminate relative to the parent laminate. Bayazeid et al [24] performed a repair methodology on CF/PEEK laminates employing induction heating. Using a custom drop test tower, the laminates were impacted at an energy of 10 J.…”
Section: Introductionmentioning
confidence: 99%